Business Plan Javana Culture Bags (JCB) Preserving the Local Wisdom of Batik Bekasi - Wulandari, Restia; Rizki, Moch; Zahra, Rayi Fatimah; Widiawati, Kristiana (Ilomata International Journal of Social Science, 2024)
Indonesia is an archipelago renowned for its natural beauty and cultural diversity. One of its most significant cultural heritages is batik, recognized by UNESCO as an intangible cultural heritage and celebrated as part of national identity on National Batik Day, October 2nd each year. Each region in Indonesia has its unique batik, such as Batik Seraci from Bekasi, introduced in 2013. However, awareness and information about Batik Seraci remain limited among the general public. To address this issue, Javana Culture Bag promotes Bekasi's cultural heritage through modern fashion products made from patchwork Batik Seraci that appeal to Generation Z. This research employs a qualitative method with a phenomenological approach to understand the experiences and perspectives of individuals related to Javana Culture Bag's products. A SWOT analysis is used to evaluate the company's internal and external environment. Javana Culture Bag's target audience includes students and office workers aged 12 to 35 in Bekasi who have an interest in fashion and art. The marketing strategy includes offline and online advertising through social media platforms such as TikTok, Shopee, and Instagram, as well as participation in exhibitions and trade shows. These products are offered at competitive prices, reflecting their quality and cultural value. Overall, Javana Culture Bag strives to preserve and promote Bekasi's batik tradition by creating modern fashion products that appeal to young consumers, while actively contributing to the local economy and cultural preservation.